Improving Transitional Services for Adolescents and Young Adults with Epilepsy and Intellectual Disability - Schraegle, William A.; Young, Stephanie R.; Rettig, Eman K.; Payne, Angie R.; Wilson, Janet K.; Wedberg-Sivam, Elizabeth A.; Titus, Jeffrey B. (Journal of Pediatric Epilepsy, 2020)
The transition from pediatric to adult health care systems is challenging for many adolescents with epilepsy and their families, and those challenges are compounded for adolescents with comorbid intellectual disabilities and epilepsy (ID-E). Many traditional transition pathways to adult care are inadequate, as they fail to address important considerations unique to the ID-E population or are absent entirely. Poor organization of care during critical transition periods increases the risks of sudden unexpected death in epilepsy, suboptimal seizure control, inadequate management of comorbidities, and poor psychological and social outcomes. The literature lacks systematic studies on effective transition programs for this population. The present review provides an overview of the main themes important in care transitions for the ID-E population: (1) precise diagnosis and management of seizures; (2) mental health and medical comorbidities affecting care; (3) accessing behavioral, habilitative, legal, financial, and community resources; and (4) caretaker support. We propose a specific framework which includes targeted recommendations of minimum care standards for youth with ID-E transitioning to adult care.
Keywords: epilepsy; transition; intellectual disability; adolescent; genetics; behavioral comorbidity; transition readiness